The wakcha hero or migrant as chakana: A classification proposal - Valle Araujo, John Harvey (2021)
The present work proposes a classification of the hero or migrant wakcha within the Andean universe, characterized by the manifestations of a mythical rationality typical of non-Western cultures. In this sense, interdisciplinary studies of the Andean oral tradition are used to first describe the particular worldview of the character and then to propose the classification of the character based on his migratory experience. For this purpose, it first describes some aspects of the Andean universe that correspond to a cyclical view of time, whose imbalance forces population displacement. Secondly, the attributes of the hero or migrant wakcha are presented as an element of an interrelated whole, according to their own worldview, and their role as chakana is established in their process of rearticulation of their universe. Finally, as a result of this research, the relevance of a classification proposal of the wakcha hero or migrant category that takes into account their migratory destination is determined.